Variation and clustering analysis of several species of soursop family (Annonaceae) based on vegetative morphology characters - Santoso, Yusuf; Probojati, Rasyadan Taufiq; Hapsari, Lia; Supandji, Supandji; Kustiani, Edy (Universitas Trunojoyo Madura, 2024)
The Annonaceae family exhibited a high level of diversity and is spread over many regions. The designation of the names of several species of the Annonaceae family varies in each region. Therefore, characterization is needed to confirm and classify the taxonomy position of the species. This study aims to characterize the variation and analyze the clustering pattern of several species of the Annonaceae based on vegetative morphology characters. The type of method used in this research is exploratory descriptive, with seventeen specimen species consisting of ten Annonaceae studied in this research. Characters observed include tree age, stem diameter, plant height, stem color, type of sapling, type of branching, leaf shape, leaf tip shape, leaf base shape, leaf width, leaf length, leaf thickness, petiole length and thickness, leaf hairs , color of young and mature leaves, type of leaf edge, number of leaf veins, color of young branches, leaf hairs on young branches, and number of nodes on the stem per meter. These qualitative and quantitative characters were observed using Descriptors for Cherimoya (Annona cherimola Mill.) from Bioversity International and CHERLA. Data analysis was conducted in the Paleontological Statistics program with cluster analysis method (Bray-curtis similarity index) to produce a dendrogram topology. Results showed that there were variations in vegetative morphological characteristics among the ten species examined. Dendrogram topology was divided into 3 groups relatively following the tribe division, with similarity index 0.64 to 0.96. Xylopia sp. was separated from the others in Group 1 (Xylopiae). Group 2 (Uvariae) consisted of Fissistigma sp., Desmos chinensis, Artabotrys suaveolens, Uvaria purpurea, and Desmos sp. Group 3 (Annoneae) consisted of Annona muricata, Annona montana, Stelechocarpus burahol, and Annona glabra. Vegetative morphological characters have proven to be useful and effective in differentiating species in the Annonaceae family; it is recommended for initial identification of species, especially in the Annonoideae subfamily.